Performance Appraisals of School Administrators in One Canadian School District: A Contemporary Model - Normore, Anthony H. (Alberta Journal of Educational Research, 2004)
Research indicates that a sound performance appraisal process for school administrators contains key mechanisms that manifest themselves through dimensions of effective planning, assessment, and evaluation; effective use of resources; and communicating clear expectations. This article documents the development of a contemporary model of performance appraisal of school administrators in a Canadian school district. It is clearly presented as a guideline for individual educators who are committed to ongoing professional development. It may well serve as a guideline for other school districts where performance appraisal processes are being revisited and revamped for purposes of accountability and school administrators' performance effectiveness.